THU0322 Descriptive study of asian indian patients with rheumatoid vasculitis in retrospect: a single, tertiary care centre experience. (15th June 2017) - Mathew, J; Ganapati, A; Goel, R; Pulikool, S; Mathew, AJ; Janardhana, R; Gowri, M; Danda, D
Abstract : Background: Rheumatoid vasculitis (RV) is a severe extra-articular manifestation of rheumatoid arthritis (RA), with high morbidity and mortality reported in literature Objectives: To describe the Asian Indian perspective on RV patients, their clinico-laboratory features and their outcome along with the factors affecting them Methods: A retrospective review of electronic medical records of 8984 RA patients from January 2007 to August 2016, was done for those satisfying Scott & Bacon criteria for RV 1 . Probable RV was defined as patients not satisfying Scott & Bacon Criteria, but were managed like RV after exclusion of alternate diagnosis. Birmingham Vasculitis activity score (BVAS) version 3 2 was used for monitoring activity of RV Results: 63 patients of RV were identified, with a study period prevalence of 0.7%, in our RA cohort. 33 (52.4%) patients were female. Mean age of patients was 50.7±11.5 years with median duration of RA being 6 years. Involvement of Peripheral Nervous System (PNS) was the commonest manifestation of RV in 52/63 (82.5%) patients followed by skin in 34/63 (53.9%) patients. Rheumatoid Nodule was seen in 14/ 63 (22.2%) patients. Percentage of current and ex-smokers combined, was same as rheumatoid nodule prevalence. 52 (82.5%) patients had biopsy evidence of vasculitis.26/51 (50.9%)patients were started on mycophenolate mofetil, 13/51 (25.5%)patients on cyclophosphamide, 8/51 (15.7%) patients on azathioprine, 4/51 (7.8%) patients on Methotrexate as immunosuppressive (IS) agent along with mean dose of 46.6±13.7 (0.86±0.23mg/kg/day) prednisolone. Additionally, Rituximab & IVIg were used in 2 patients each respectively. 3 months after initiation of immunosuppression 26/50 (52%) patients on follow-up were in remission and 39/47 (82.9%) patients attained remission at 6 months. Mean time to achieve remission was 151.1±86.3 days. All IS agents were equally effective in inducing remission at 3 and 6 months and showed statistically similar BVAS reduction at 3 and 6 months from baseline (t test & chi-square test). 7 (11.2%) deaths noted in the cohort at their respective last visit during 195.3 patient years cumulative follow up. Multiple regression analysis showed that at baseline, presence of PNS involvement, eosinophilia, thrombocytosis, higher BVAS score and higher steroid requirement were predictors of persistently active vasculitis and absence of eye involvement and higher hemoglobin % at baseline were predictors for remission, at 3 months (p<0.05). 4/50 (8%) patients had relapse of vasculitic symptoms. 2 and 5 year survival rates were 96.2% and 83.9% respectively Conclusions: Our cohort of Asian Indian RV was comparitively younger with lesser RA duration, less percentage of ever-smokers, lesser rheumatoid nodule prevalence, higher PNS involvement with better survival/mortality rates compared to published literature. All IS agents showed equal rates of BVAS remission & BVAS reduction at 3 and 6 months of treatment References: Scott DG, Bacon PA. Intravenous cyclophosphamide plus methylprednisolone in treatment of systemic rheumatoid vasculitis. Am J Med. 1984 Mar;76(3):377–84. Mukhtyar C, Lee R, Brown D, Carruthers D, Dasgupta B, Dubey S, et al. Modification and validation of the Birmingham Vasculitis Activity Score (version 3). Ann Rheum Dis. 2009 Dec;68(12):1827–32. Disclosure of Interest: None declared